(untitled) (Nexo Revista Científica, 2020)
To study the effect of sowing date and water stress on qualitative traits of canola, an experiment was conducted for two years in Iran. The sowing date and irrigation were in two levels as the main factors, and five canola cultivars and hybrids were included as the subfactors. In normal sowing date and normal irrigation conditions, The Tassilo hybrid with a high seed yield and seed oil yield (6139 and 2905 kg ha-1, respectively) can be effective in the cultivation of canola in temperate cold regions with dry and semi-arid climates. In the conditions of delayed cultivation and late season drought stress, the same hybrid with the highest seed yield and seed oil yield (2935 and 1273 kg ha-1, respectively) and the least amount of erucic acid (0.4%) and glucosinolate content (22.9 μmol g-1) is recommended for the delayed cultivation conditions together with late season drought stress.